GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 70355 species occurrences available in GBIF matching the query: TaxonKey: Apodemus sylvaticus (Linnaeus, 1758). The dataset includes 70355 records from 263 constituent datasets: 4 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 14 records from Ghent University - Zoology Museum - Vertebrate collection. 4 records from SUI Vertebrate Collection. 7 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 10 records from Mid Ulster Hare Surveys 2012-2015. 1 records from ISM Mammalogy Collection. 20 records from African Rodentia. 3 records from uconn-mammals. 198 records from MVZ Mammal Collection (Arctos). 3 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 8 records from Australian National Wildlife Collection provider for OZCAM. 253 records from Small Mammal Research Database. 10 records from Zoology (Museum of Evolution - Uppsala). 302 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 8 records from BioGIS - Mammals - INPA database. 87 records from KUBI Mammalogy Collection. 1 records from Local BioBlitz Challenge 2013. 1 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 3232 records from Inventario Español de Especies Terrestres (MAGRAMA). 5374 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 2 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 50 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 32 records from BioFokus. 2 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 8 records from CUMV Mammal Collection (Arctos). 12 records from UAM Mammal Collection (Arctos). 119 records from Artdata. 4 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 2779 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Museum Victoria provider for OZCAM. 2 records from Cowan Tetrapod Collection - Mammals. 220 records from Field Museum of Natural History (Zoology) Mammal Collection. 2952 records from Lund Museum of Zoology (MZLU). 52 records from Données ONF Faune-Flore-Fonge. 66 records from Norwegian Biodiversity Information Centre - Other datasets. 2493 records from Naturalis Biodiversity Center (NL) - Mammalia. 71 records from Museum of Comparative Zoology, Harvard University. 1 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 29 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 5 records from iNaturalist Research-grade Observations. 2 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 111 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 7 records from University of California Museum of Paleontology. 2238 records from Mammals housed at MHNG, Geneva. 1 records from KUBI Vertebrate Paleontology Collection. 52 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 1626 records from NMNH occurrence DwC-A. 2 records from DMNS Mammal Collection (Arctos). 509 records from Mammal collection, Natural History Museum, University of Oslo. 1 records from Klasse 3a. 1 records from Beweidungsprojekt an der Nesse. 1 records from Ehmkendorf. 1 records from Feriendorf des Kreises Gedern (Ober-Seemen). 1 records from Lassentiner Moor (Niepars). 1 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from Artenvielfalt Kreis Gießen. 1 records from Alter Nördlicher Friedhof (München). 1 records from Wangerooge. 1 records from Wirbach. 1 records from Landschaftsschutzgebiet Buchhorst 3. 1 records from Bolzplatz. 1 records from Erft in Selikum (Neuss). 1 records from Spießwoogtal / Königsbruch (Fischbach). 1 records from Schwanseepark (87645 Schwangau). 1 records from Mauernacker (Wettsaasen). 1 records from Dalbekschlucht. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Gelände des Schulzentrums am Himmelsbarg. 2 records from Römertal (Steinpleis). 2 records from Klütwald. 1 records from Sudeniederung (Amt Neuhaus). 1 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 1 records from Landschaftsschutzgebiet Buchhorst 4. 3226 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 1 records from FFH-Gebiet Klosterwasser/Burkau. 2 records from CM Vertebrate Paleontology Collection. 102 records from The Mammal Society - National Mammal Atlas Project, online recording. 444 records from naturgucker. 139 records from Vertebrats d'Andorra. 106 records from UMMZ Mammal Collection. 7 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 2 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Schulgelände des Schulzentrums am Himmelsbarg. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Schieferbrüche. 12 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 256 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 11 records from MfN - Fossil vertebrates IV. 200 records from Mammal Collection. 4 records from SBMNH Vertebrate Zoology. 37 records from LACM Vertebrate Collection. 70 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Artenvielfalt rund um die Dalbek-Schule. 6 records from Mammals (NSMK-MM). 5 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 43 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 1 records from SysTax - Zoological Collections. 9344 records from Natural History Museum (London) Collection Specimens. 80 records from Mammalia fossil Kleinsäuger - SMF. 13 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 25 records from Ireland's BioBlitz. 3 records from ISU Mammals. 2 records from Collection Anatomie Histologie - SMF. 5 records from UWBM Mammalogy Collection. 14 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 367 records from Museo Nacional de Ciencias Naturales, Colección de Mamíferos: MNCN-Mam. 6 records from Database on Forest Disturbances in Europe. 2 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 91 records from Paleobiology Database. 1 records from Mammals Specimens. 4 records from FHSM Mammals Collection. 1 records from CNMA/Colección Nacional de mamíferos. 15 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 888 records from TTU Mammals Collection. 1 records from GEO Biodiversity Day. 11 records from Israel Nature and Parks Authority. 1602 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 3347 records from Estacion Biologica Donana - CSIC, Mammal Collection. 1 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1 records from inatura - Erlebnis Naturschau Dornbirn. 4 records from Staffordshire Ecological Record - SER Site-based Surveys. 2 records from WNMU Mammal Collection (Arctos). 4 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 1 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from Trockenhang Greinhartsberg Edelfingen. 1 records from Hamberger Brücke / Würmtal (Pforzheim). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Mooswald (Freiburg). 1 records from Gemeinde Sursee. 1 records from Angelberger Forst - Klassen 3 a und 3 b. 1 records from Naturschutzgebiet Bausenberg. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Königstetten. 1 records from Erzental (Oberotterbach). 2 records from Langes Tannen (Uetersen). 1 records from Neckartalsüdhang (Horb). 1 records from Langes Tannen. 1 records from Philosophenwald und Wieseckaue in Gießen. 1 records from Artenvielfalt auf Restbauernhof. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from katzenbuckel. 1 records from Biologische Station im Kreis Wesel. 1 records from GEO-Hauptveranstaltung (Duisburg). 1 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Pilstingermoos. 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 1 records from Schulhof Goethe-Gymnasium (Emmendingen). 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Faberpark (Nürnberg/Stein). 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 1 records from Lüner Holz (Lüneburg). 1 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 1 records from Prophetensee Quickborn. 1 records from Spandau HBO. 1 records from Dreilinden Gymnasium-Schulgelände. 1 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Tag der Artenvielfalt. 506 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 7 records from Occurrence of mammalia relicts at site Pestera Cioarei. 5 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 1 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 4 records from Occurrence of mammalia relicts at site Raj Cave. 1 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 1 records from Occurrence of mammalia relicts at site Veternica. 3 records from Occurrence of mammalia relicts at site Velika Pecina. 5 records from Occurrence of mammalia relicts at site Sütto_6. 3 records from Occurrence of mammalia relicts at site Kalman Lambrecht Cave. 1 records from Occurrence of mammalia relicts at site Poroslyuk. 2 records from Occurrence of mammalia relicts at site Remetehegy. 4 records from Occurrence of mammalia relicts at site Rejtek 1. 1 records from Occurrence of mammalia relicts at site Felsställe. 2 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 2 records from Occurrence of mammalia relicts at site Stematia. 1 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 1 records from Occurrence of mammalia relicts at site Kartstein. 3 records from Occurrence of mammalia relicts at site Ettingen. 1 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 2 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 1 records from Occurrence of mammalia relicts at site l´Abri du Morin. 2 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 4 records from Occurrence of mammalia relicts at site Roc de Combe. 5 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 1 records from Occurrence of mammalia relicts at site Petnicka Pecina. 2 records from Occurrence of mammalia relicts at site Smolucka Pecina. 1 records from Occurrence of mammalia relicts at site Genkingen 2. 1 records from Occurrence of mammalia relicts at site Vraona Cave. 7 records from Occurrence of mammalia relicts at site Pestera Cioarei. 1 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 1 records from Occurrence of mammalia relicts at site Nikolaushöhle. 1 records from Occurrence of mammalia relicts at site Burgtonna. 1 records from Occurrence of mammalia relicts at site Spitalhöhle. 4 records from Occurrence of mammalia relicts at site Grotte Scladina. 2 records from Occurrence of mammalia relicts at site Pestera Magura. 1 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 1 records from Occurrence of mammalia relicts at site Pestera Livadita. 3 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 16 records from Occurrence of mammalia relicts at site Pestera la Adam. 5 records from Occurrence of mammalia relicts at site Pestera Hotilor. 1 records from Occurrence of mammalia relicts at site Nazeing. 1 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1 records from Occurrence of mammalia relicts at site Felslindlhöhle. 4 records from Occurrence of mammalia relicts at site Einhornhöhle. 1 records from Occurrence of mammalia relicts at site Ochtendung. 4 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 2 records from Occurrence of mammalia relicts at site Felsställe. 15 records from PSM Vertebrates Collection. 1 records from Perchtoldsdorfer Heide. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 1 records from Klosterwald Itzehoe. 6 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 31 records from EDIT - ATBI in Gemer area (Slovakia). 20 records from DOF. 424 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 11722 records from Mammals in MZNA-VERT: pellet sampling. 181 records from Mammals in MZNA-VERT: project Loza. 4 records from UAZ Mammals. 957 records from Biological and palaeontological collection and observation data MNHNL. 5660 records from Collection Mammalia SMF. 3 records from DOF 2001-2006. 494 records from AMNH Mammal Collections. 2 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 15 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 2 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 5 records from Mammal Specimens. 15 records from Terrestrial vertebrates. 17 records from ArtenFinder. 2 records from Auckland Museum Land Vertebrates Collection. 117 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 35 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 16 records from BioGIS - Mammals - HUJ collections. 6 records from National Trust - Ickworth species data held by The National Trust.. 612 records from Norwegian Species Observation Service. 154 records from MSB Mammal Collection (Arctos). 137 records from Mammals in MZNA-VERT: project CAS. 1 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 508 records from Staffordshire Ecological Record - SER Species-based Surveys. 1127 records from Atlas of Mammals in Ireland 2010-2015. 216 records from Mammalogy Collection - Royal Ontario Museum. 105 records from Mammals in MZNA-VERT: project Biodiversity of mammals in Pamplona. 2 records from IICT Colecção Zoológica. 1 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 4 records from University of Alberta Museums, Mammalogy Collection. 52 records from Données ONF Faune-Flore-FOnge. 1636 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 11 records from National System of Protected Areas in Poland - Animals. 6 records from Australian Museum provider for OZCAM. 1 records from National Trust - Heigham Holmes species data held by The National Trust. 5 records from Anymals+plants - Citizen Science Data. 545 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1 records from Baekdu Mountain Animal. 1 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 650 records from Dutch Mammal Society (NL) - Mouse observations of life trap studies extracted from historic reports. 208 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 6 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 31 records from Data collected on scitizen science web portal www.ornitho.cat. 2 records from Collection Mammalogie - ZSRO. 345 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 36 records from South Australian Museum Australia provider for OZCAM. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences